2017
DOI: 10.1007/s00520-017-3879-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between phase I study duration and symptom burden

Abstract: AEs may lead to early termination of trial participation and confound clinical assessment of investigational treatments. Designing interventions to reduce AE burden may extend duration on trial, affect the recommended phase II dose, and benefit the quality of life of participants on phase I trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Symptom burden has been previously reported to increase as patients participate in clinical trials, which was also true in our study. 23 We did not see significant differences between intervention and control groups in symptoms, as measured by the FACT-G physical well-being (PWB) subscale.…”
Section: Dropoutsmentioning
confidence: 66%
See 1 more Smart Citation
“…Symptom burden has been previously reported to increase as patients participate in clinical trials, which was also true in our study. 23 We did not see significant differences between intervention and control groups in symptoms, as measured by the FACT-G physical well-being (PWB) subscale.…”
Section: Dropoutsmentioning
confidence: 66%
“…Finally, patients often have worsening performance status and increasing symptoms as their cancer progresses. [19][20][21][22][23][24] We previously tested a palliative care intervention (PCI) delivered by nurses who recruited and consented patients and caregivers, did baseline PC assessments, worked with an interdisciplinary team (IDT) to create a care plan, and did two teaching sessions with a standardized workbook. 25 In this study, we applied the PCI to a new population of Phase I patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al [52] found that patients referred for ECMTs have a similar symptom burden to those who were not, despite the perception of higher levels of fitness. A high symptom burden has also been associated with early discontinuation from trials [53], highlighting the potential role for supportive care. Br edart et al [54] suggested that this patient group is more likely to accept increased toxicity to facilitate continued access to trial drugs.…”
Section: The Importance Of Supportive Care In Experimental Cancer Medicinementioning
confidence: 99%
“…Patients who could continue after two cycles may have had less aggressive deterioration of their disease or experienced clinical benefit. Earlier research showed that the patients who continued could have experienced fewer side-effects of the investigated agents, since they had fewer symptoms of their disease to start with (Anwar et al, 2017;Treasure et al, 2018).…”
Section: Discussionmentioning
confidence: 99%